Correlation Between Maternal Knowledge Of Exclusive Breastfeeding And Breastfeeding Pattern At Waru Primary Healthcare Center Sidoarjo In 2017 - Santos, Vilma IAJM dos; Tirtahusada, PY Kusuma; Rihadi, Lukas Slamet (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: Globally, the rate of child mortality is mostly due to recurrent infection and nutritional factors. Promotion of exclusive breastfeeding and appropriate weaning food can reduce the risk of getting a chronic disease and under-5 mortality and morbidity. Exclusive breastfeeding means giving only breast milk without adding and/or replacing it with any other food or drink (except drugs, vitamins, and minerals). Exclusive breastfeeding has many benefits both for mother and infant. Aim: This study was to investigate the correlation between maternal knowledge about breastfeeding and breastfeeding pattern among breastfeeding mothers at Waru Primary Healthcare Center Sidoarjo. Methods: This study is an observational analytical study employing cross-sectional design and Spearman correlation for data analysis. This study was conducted at Waru Primary Healthcare Center Sidoarjo between August and September 2017. This study was conducted in a total of 100 participants. This research used a questionnaire as an instrument. Resulta: The result showed a significant correlation (p = 0,049). Thus it can be concluded that there is a correlation between mother's knowledge level about breastfeeding with mother breastfeeding pattern at Waru District Health Center Sidoarjo. The correlation coefficient value (r=0.197) indicates that the positive correlation is very weak between the mother's knowledge level and the pattern of the lactating mother. Conclusion: These results indicate that the higher the level of mother's knowledge, the higher the pattern of breastfeeding mothers. Increased knowledge and breastfeeding patterns may reduce the risk of chronic illness, morbidity and mortality rates among under-fives. This research can be useful for education, and it is expected that health workers can cooperate with the government in promoting exclusive breastfeeding.